Critically engaging engineering in place by localizing counternarratives in engineering design. Issue 3 (8th February 2019) - Nazar, Christina Restrepo; Barton, Angela Calabrese; Morris, Caleb; Tan, Edna
Abstract: In this manuscript, we use the construct of critical epistemologies of place to frame our exploration of how to support engineering design among youth who have historically been marginalized from the domain, and its implications for educational settings. We present an in‐depth longitudinal case study of one 12‐year‐old African American boy to raise questions of what it means for this youth to engage in engineering design in collaboration with the people around in him—experts and knowledgeable others in his community space and how this engagement supports his work in science and engineering. This study suggests that engaging engineering design through a critical epistemology of place involves an iterative and generative process of layering community wisdom and knowledge onto STEM toward (a) how epistemologies of place—and their layers—challenge dominant master narratives, (b) reimagining practices in place, and (c) transforming the dangerous territory of STEM. Our study expands upon current understandings of supporting youth in engaging engineering through highlighting the vital role of sociohistorically constructed understandings of STEM and community in determining when, how, and why engineering takes place.